Sea Floor of the Marine Protected Area of the Asinara Island (Sardinia, Italy). Issue 2 (1st December 2022) - De Luca, Mario; Pascucci, Vincenzo; Puccini, Alessandra; Pireddu, Laura; Santonastaso, Antonio; Stelletti, Myriam; Gazale, Vittorio; Zanello, Aldo
ABSTRACT: The Asinara Island Marine Protected Area (AMP) (Sardinia, Italy) represents one of the most uncontaminated areas of the Mediterranean Sea and, therefore, but misses of an accurate mapping of the biocenoses and associated lithologies present on the sea floor. The provided map has highlighted the presence of 21 biocenoses laying on rocky or sandy substrate if shallower or deeper respectively. The most recurring are: the Posidonia oceanica L (Delile) and the coralligenous. The good state of conservation the P. oceanica meadow characterizing the eastern part of the island, and the diffuse presence Coralligenous reefs on the western side, are indicative of the well conditions of the marine ecosystem of the Asinara Marine Protect area. Moreover, the Coralligenous reefs developed on beach rocks have allowed defining which was the paleogeography of the Asinara Island during the time interval comprised from 12.9 to 10.0 ka Before Present (BP).